IMPLEMENTATION OF THE 'æ•°å—ç´ å…» (SHÃ™ZÃŒ SÃ™YÇNG)' INSTRUMENT TO MEASURE THE DIGITAL LITERACY LEVEL OF MANDARIN LANGUAGE EDUCATION STUDENTS - Ventivani, Aiga; Muyassaroh, Lukluk Ul; Laksana Sakti, Karina Fefi; Masrur, Muhammad Farhan (UNDIKMA, 2025)
The current presence of the internet undeniably facilitates and accelerates individuals' ability to access and disseminate information, even leading to an information explosion. To manage this situation, digital competence is required to face the 6.0 era. The world's shift toward complete digitalization pushes humans to quickly adapt to digital infrastructure and digital services. To address this, humans need skills referred to as digital literacy. This research emphasizes the measurement of primary data, specifically objective digital literacy levels, using numerical data and statistical analysis. The study aims to determine the digital literacy level of Mandarin language students using the